Long-term evaluation of palm oil mill effluent (POME) steam reforming over lanthanum-based perovskite oxides - Cheng, Yoke Wang; Chong, Chi Cheng; Cheng, Chin Kui; Wang, Chi Hwa; Ng, Kim Hoong; Witoon, Thongthai; Lam, Man Kee; Lim, Jun Wei (Academic Press, 2024)
To replace the obsolete ponding system, palm oil mill effluent (POME) steam reforming (SR) over net-acidic LaNiO3 and net-basic LaCoO3 were proposed as the POME primary treatments, with promising H2-rich syngas production. Herein, the long-term evaluation of POME SR was scrutinized with both catalysts under the optimal conditions (600 °C, 0.09 mL POME/min, 0.3 g catalyst, & 74–105 μm catalyst particle size) to examine the catalyst microstructure changes, transient process stability, and final effluent evaluation. Extensive characterization proved the (i) adsorption of POME vapour on catalysts before SR, (ii) deposition of carbon and minerals on spent SR catalysts, and (iii) dominance of coking deactivation over sintering deactivation at 600 °C. Despite its longer run, spent LaCoO3 (50.54 wt%) had similar carbon deposition with spent LaNiO3 (50.44 wt%), concurring with its excellent coke resistance. Spent LaCoO3 (6.12 wt%; large protruding crystals) suffered a harsher mineral deposition than spent LaNiO3 (3.71 wt%; thin film coating), confirming that lower reactivity increased residence time of reactants. Transient syngas evolution of both SR catalysts was relatively steady up to 4 h but perturbed by coking deactivation thereafter. La2O2CO3 acted as an intermediate species that hastened the coke removal via reverse Boudouard reaction upon its decarbonation. La2O2CO3 decarbonation occurred continuously in LaCoO3 system but intermittently in LaNiO3 system. LaNiO3 system only lasted for 13 h as its compact ash blocked the gas flow. LaCoO3 system lasted longer (17 h) with its porous ash, but it eventually failed because KCl crystallites blocked its active sites. Relatively, LaCoO3 system offered greater net H2 production (72.78%) and POME treatment volume (30.77%) than LaNiO3 system. SR could attain appreciable POME degradation (>97% COD, BOD5, TSS, & colour intensity). Withal, SR-treated POME should be polished to further reduce its incompliant COD and BOD5.